2017
DOI: 10.1177/1369433217693631
|View full text |Cite
|
Sign up to set email alerts
|

Improving double-layer space trusses collapse behavior by strengthening compression layer and weakening tension layer members

Abstract: Progressive collapse is a chain of local failures leading to the collapse of either the entire or a part of the structure. The double-layer space trusses are susceptible to progressive collapse due to sudden buckling of compression members. The method of strengthening the compression layer members along with weakening the tension layer members is an effective method for retrofitting the double-layer space truss behavior against progressive collapse. In this study, the method is applied on offset double-layer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Due to the recent failures of progressive collapse in DLST structures, several researchers are working on ways to improve the performance of the space truss behaviour by achieving a much smoother and ductile response of the structure. The results by [6] show that the method of strengthening the compression layer members along with weakening the tension layer members is an effective method for retrofitting the DLST behaviour against progressive collapse. [7] highlighted that material and geometric nonlinearities are important factors to be considered in the collapse behaviour of space truss structures.…”
Section: Novel Soft Membermentioning
confidence: 99%
“…Due to the recent failures of progressive collapse in DLST structures, several researchers are working on ways to improve the performance of the space truss behaviour by achieving a much smoother and ductile response of the structure. The results by [6] show that the method of strengthening the compression layer members along with weakening the tension layer members is an effective method for retrofitting the DLST behaviour against progressive collapse. [7] highlighted that material and geometric nonlinearities are important factors to be considered in the collapse behaviour of space truss structures.…”
Section: Novel Soft Membermentioning
confidence: 99%
“…The vertical eccentricity E2 is proportional to the angle ϕ, being equivalent to the correction distance d. Figure 8 shows that the measurement of d2 is equal to 5t1 of the pipe wall thickness (flange) Several other collapses in 3D trusses have been observed in the world. However, the ranges of space truss structures have been reevaluated and some have been strengthened in recent years [61][62][63][64][65][66][67][68][69][70], thanks to increasingly robust computer systems and commercial Finite Element Method (FEM) programs and complex nonlinear analyses [10,30,56,[71][72][73][74][75][76][77][78][79][80][81][82].…”
Section: Correction Of Eccentricity In Typical Connectionsmentioning
confidence: 99%
“…This delays the failure of the compression members and consequently a good level of ductility will be provided [4]. A comprehensive study regarding this method is conducted by Rashidyan and Sheidaii [10].They used this method on five DLST models with various conditions. They showed that 30%-40% overdesign of all top and under design of bottom members results in satisfactory ductility level and load bearing capacity in their investigated models.…”
Section: Introductionmentioning
confidence: 99%
“…Second, DLSTs with overall collapse behavior having different member imperfection and FLD activation level are analyzed to examine the effect of such factors on the effectiveness of using FLDs. In the end, the results of this study were also compared to another retrofitting method called the method of over designing the members of compression layer and under designing the members of tension layer to improve the collapse behavior of flat DLSTs suggested by Rashidyan and Sheidaii [10]. Since the DLST models used in both studies are the same, the comparison of the results can help obtaining more insight regarding the effectiveness of installing FLDs on DLSTs.…”
Section: Introductionmentioning
confidence: 99%